Indonesian HIV women's perception about HIV- transmitted prevention in pregnancy intention: a peer support group survey - Koeryaman, Mira Trisyani; Melinda, Yuyun; Sutini, Titin (Universitas Aisyah Pringsewu, 2024)
In Bandung city, the prevalence of HIV-positive women increased annually. It can potentially produce an infected fetus if they are pregnant because HIV (human immunodeficiency virus) can pass through the placenta and transmit to the fetus. With women's awareness, preventing transmission risk may be beneficial to achieve a safe conception, pregnancy and birth for women who are planning to have a baby. Aims. This study aims to identify HIV women's perception of the perinatal spread of HIV in pregnancy and highlights their role in managing transmission prevention. Method. Fifty-two women with diagnosed HIV belonging to active members of a peer support group (PSG) in Bandung city, Indonesia, answered survey questionnaires. The questions covered behaviors components on perceived HIV-transmitted risk, benefits and obstacles and self-confidence in HIV-transmitted prevention (5-point scale). The data collection was carried out about two months. Results. Participants generally have a positive perception of HIV-transmitted prevention. Of the 52 women, 51.4% (n=27) showed positive perceptions of HIV-transmitted susceptibility, 60% (n=30) felt no barriers to HIV-transmitted prevention, and 51.4% (n=27) had positive self-confidence in HIV-transmitted prevention. In contrast, 54.3% of women (n=28) indicated that they negatively perceive the benefits of HIV- transmitted prevention. Conclusions. These findings provide important clues for planning HIV management before pregnancy, highlighting the domains that health professionals should seriously focus on in giving proper intervention. Health professionals should use specific strategies to promote the benefits of HIV-transmitted prevention to achieve the demands of safe conception, pregnancy and postpartum.